2020
DOI: 10.3389/fgene.2020.589413
|View full text |Cite
|
Sign up to set email alerts
|

RNA, Genome Output and Input

Abstract: RNA, the transcriptional output of genomes, not only templates protein synthesis or directly engages in catalytic functions, but can feed back to the genome and serve as regulatory input for gene expression. Transcripts affecting the RNA abundance of other genes act by mechanisms similar to and in concert with protein factors that control transcription. Through recruitment or blocking of activating and silencing complexes to specific genomic loci, RNA and protein factors can favor transcription or lower the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Alternatively, contact-independent E-P communication has been proposed, a model in which information present at cis -regulatory regions is transferred to promoters even at a distance, for example by diffusion of post-translationally modified TFs at enhancers ( Karr et al, 2021 ). Enhancer RNAs or condensates may similarly facilitate transcriptional activation at a distance ( Morf et al, 2020 ). Although contact-independent E-P communication requires greater experimental validation, it offers a theoretical framework compatible with recent findings.…”
Section: Enhancer-promoter Interactions Could Be Spatiotemporally Dec...mentioning
confidence: 99%
“…Alternatively, contact-independent E-P communication has been proposed, a model in which information present at cis -regulatory regions is transferred to promoters even at a distance, for example by diffusion of post-translationally modified TFs at enhancers ( Karr et al, 2021 ). Enhancer RNAs or condensates may similarly facilitate transcriptional activation at a distance ( Morf et al, 2020 ). Although contact-independent E-P communication requires greater experimental validation, it offers a theoretical framework compatible with recent findings.…”
Section: Enhancer-promoter Interactions Could Be Spatiotemporally Dec...mentioning
confidence: 99%
“…Apart from a set of highly conserved and functionally characterised lncRNAs [35], lncRNAs show low sequence conservation. Hence, some may be functionless, function by the act of transcription itself [21,36,37], like the bidirectionally transcribed class of eRNAs [38], or have short functional elements that escape common conservation analyses. Some of the highly conserved lncRNAs identified in this work have been experimentally tested in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancer transcription is considered the best molecular indicator of enhancer activity in developmental processes (Wu et al, 2014;Arner et al, 2015;Kim et al, 2015;Carullo et al, 2020;Sartorelli and Lauberth, 2020) and cancers (Chen and Liang, 2020). There has been uncertainty about whether the resulting eRNAs are byproducts of TF binding at enhancers or are integral to enhancer action (Li et al, 2016;Schoenfelder and Fraser, 2019), but the evidence is now strongly in favor of the latter, although it is also clear that the act of transcription itself modulates enhancer activity (Pande et al, 2018;Morf et al, 2020;Pande et al, 2020). While genetic analysis by enhancer deletion may not distinguish between the loss of cis-acting DNA regulatory elements and transacting elncRNAs (Gao et al, 2020;Andergassen and Rinn, 2021), more incisive strategies such as the insertion of polyA transcription termination sites, removal of elncRNA exons, siRNA-and CRISPRi/ Cas13-directed RNA knockdown have shown that elncRNAs are required for enhancer function in diverse contexts (Maass et al, 2012;Li et al, 2013;Melo et al, 2013;Lam et al, 2014;Paralkar et al, 2014;Sun et al, 2014;Xiang et al, 2014;Yin et al, 2015;Yang et al, 2016;Isoda et al, 2017;Cajigas et al, 2018;Groff et al, 2018;Fatima et al, 2019;Lewandowski et al, 2019;Allou et al, 2021;Andergassen and Rinn, 2021;Cajigas et al, 2021;Setten et al, 2021;Zibitt et al, 2021).…”
Section: Transcription From Enhancersmentioning
confidence: 99%